Prodi Administrasi Publik, Fakultas Ilmu Sosial, Universitas Muhammadiyah Gorontalo - Bilondatu, Susanti; Mohi, Widya Kurniati; Karim, Dian Fitriani; Akibu, Rifka S. (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Bhayangkara Surabaya, 2025)
This research aimed to examine and identify the internal communication patterns effecting employee performance at the Regional Secretariat Office of Gorontalo Regency. The study employed a qualitative approach with descriptive research. The primary data sources included the Assistant III for General Administration of the Regional Secretary, Head of the General Subdivision, Head of the Protocol Subdivision, General Section Staff, Protocol Section Staff and Policy Analysts. Data collection methods involved observations, interviews, and documentation. The results indicated that the internal communication patterns at the Regional Secretariat Office of Gorontalo Regency were not accurate and responsive This was evident from the vertical communication pattern, which showed inaccuracies and a lack of responsiveness. This left staff confused and unclear about the instructions communicated by leadership. As a result, confusion arose that affected the execution of daily tasks Employee performance tended to decline because time and energy were wasted on seeking clanty or addressing mistakes caused by poorly understood instructions. In terms of horizontal communication, negative dynamics among colleagues at the same level were observed, such as small exclusive groups, a tendency to avoid conflict, and allowing conflicts to persist without resolution, which hindered optimal teamwork Employee performance was impacted due to a lack of synergy in completing joint tasks and regarding diagonal communication, inaccuracies and lack of transparency in cross-division and hierarchical communication hampered coordination and team collaboration communication between divisions and across hierarchies was still not accurate and responsive. On the ground, vanous challenges affected its efficiency and effectiveness The lack of transparency from leadership resulted in miscommunication across divisions. hindering timely task completion. Employees who felt they did not receive clear information or adequate support might become frustrated, negatively impacting their motivation and performance. Keywords: Internal Communication Patterns; Employee Performance; Organization